Method for improving efficiency of TOPCON battery
By adopting three-deposition and propulsion process solutions in TOPCON battery production and optimizing screen printing patterns, the problem of low efficiency of traditional boron diffusion processes is solved, and the photoelectric conversion efficiency of solar cells is significantly improved.
Patent Information
- Application Number
- CN202411548933.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The traditional boron diffusion process is relatively low in the production of crystalline silicon solar cells, affecting the photoelectric conversion efficiency of the battery.
The process scheme of three-deposition and three-propulsion is adopted to optimize the deposition and propulsion process of silicon wafers, and the number of fine grids and the line width of fine grids are increased in screen printing.
It improves the photoelectric conversion efficiency of solar cells, enhances the uniformity of boron diffusion and blue light response capabilities, and maintains the stability of the production line.
Smart Images

Figure CN119451274A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of crystalline silicon solar cells, and in particular to a method for improving the efficiency of TOPCON cells. Background Art
[0002] Photovoltaic power generation has become one of the cleanest energy sources in the world with the lowest cost and the best safety and environmental protection. In the future, with the continuous adjustment of the energy structure of various countries, the proportion of renewable energy in energy consumption is bound to increase. Among the many types of renewable energy, photovoltaic power generation technology has the greatest potential for reducing costs and increasing efficiency. Single solar cells cannot be used directly as a power source. Several single cells must be connected in series and parallel and tightly sealed into components. Combine solar cells or solar cells of different specifications cut by laser cutting machines or steel wire cutting machines, and encapsulate them in a stainless steel, aluminum or other non-metallic frame, install the glass on the top and the back plate on the back, fill with nitrogen, and seal. The whole is called a component, that is, a photovoltaic component or a solar cell component.
[0003] At present, commercial high-efficiency crystalline silicon cells are mainly divided into perc, TopCon, IBC and HJT according to their structures. In comparison, the biggest advantage of Topcon structure cells is that they have the highest potential efficiency and are closest to the theoretical limit efficiency of crystalline silicon cells. Therefore, the industry has great expectations for them. TOPCon structure cells have also become one of the key research directions for industrial high-efficiency solar cells. In the production process of crystalline silicon solar cells, the photoelectric conversion efficiency of solar cells has a significant impact on manufacturing companies. Improving the conversion efficiency of solar cells is a long-term task. In the preparation process of N-type crystalline silicon solar cells, a boron diffusion process is generally used to make PN junctions. For the boron diffusion process, not only does the boron content in the prepared PN junction have an important influence on the performance and efficiency of N-type crystalline silicon solar cells, but the uniformity of boron diffusion will also affect the parameter control of subsequent manufacturing processes. Conventional production line boron diffusion is completed using a three-step deposition + one-step advancement method; the corresponding screen-printed front pattern is 16BB-172 grid. However, the traditional boron diffusion process has the disadvantage of low efficiency. Summary of the invention
[0004] The purpose of this application is to provide a method for improving the efficiency of TOPCON cells, specifically including optimization of the front surface diffusion process and optimization of the metallization pattern for collecting and exporting current. The improved process will not have an adverse effect on the existing production line, but can significantly improve the conversion efficiency.
[0005] In order to solve the above technical problems, the technical solution adopted in this application is:
[0006] The present application provides a method for improving the efficiency of TOPCON cells, characterized by comprising depositing, advancing and screen printing a silicon wafer;
[0007] The deposition includes three depositions: in the first deposition step, the O2 flow rate is 500-580sccm, the BCl3 flow rate is 70-190sccm, in the second deposition step, the O2 flow rate is 500-600sccm, the BCl3 flow rate is 100-210sccm, and in the third deposition step, the O2 flow rate is 520-640sccm, the BCl3 flow rate is 120-230sccm;
[0008] The advancement includes three steps: the temperature of the first advancement step is 840-900°C, the temperature of the second advancement step is 860-920°C, and the temperature of the third advancement step is 870-930°C.
[0009] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0010] 1. The improvement of the amount of O2 and BCl3 introduced in the three deposition steps in this application can reduce the surface concentration of the substrate and increase the blue light response and contact ability.
[0011] 2. The present application adjusts the traditional one-time total advancement into three-time distributed advancement and combines it with step temperature rise. The step temperature rise advancement process is beneficial to the control of the depth of boron ion advancement, making the uniformity of boron diffusion better, and the improved boron diffusion process time remains unchanged, so there is no adverse effect on production capacity.
[0012] 3. This application changes the 172 grid lines of traditional screen printing to 196 grid lines. Through line width design, the front shading area remains consistent with that before the improvement, and has no effect on the light-receiving surface; however, through dense grid design, the transmission distance of carriers in the thin layer is reduced, the transmission loss is reduced, and the conversion efficiency is improved by 0.081%.
[0013] In summary, compared with the traditional boron diffusion and metallization patterns, the improved process of the present application does not produce adverse effects, but can significantly improve the conversion efficiency and is worthy of popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The metallization pattern of the control group of the experimental example of this application;
[0016] Figure 2 The metallization pattern of the experimental group of the experimental example of this application;
[0017] Figure 3 The matrix doping depth and doping concentration curve of the control group of the experimental example of this application;
[0018] Figure 4 This is the matrix doping depth and doping concentration curve of the experimental group of the experimental example of this application. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0021] A method for improving the efficiency of TOPCON cells, including deposition, advancement and screen printing of silicon wafers;
[0022] The deposition includes three depositions: in the first deposition step, the O2 flow rate is 500-580sccm, the BCl3 flow rate is 70-190sccm, in the second deposition step, the O2 flow rate is 500-600sccm, the BCl3 flow rate is 100-210sccm, and in the third deposition step, the O2 flow rate is 520-640sccm, the BCl3 flow rate is 120-230sccm;
[0023] The advancement includes three steps: the temperature of the first advancement step is 840-900°C, the temperature of the second advancement step is 860-920°C, and the temperature of the third advancement step is 870-930°C.
[0024] In some embodiments of the present application, the temperatures of the six heating zones in the first deposition step are set to 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, and the deposition time is 80-130s.
[0025] In some embodiments of the present application, the temperatures of the six heating zones in the above-mentioned second deposition step are set to 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, and the deposition time is 180-230s.
[0026] In some embodiments of the present application, the temperatures of the six heating zones in the third deposition step are set to 825-885°C, 825-885°C, 825-885°C, 825-885°C, 825-885°C, 825-885°C, and the deposition time is 180-230s.
[0027] In some embodiments of the present application, the temperatures of the six heating zones of the first advancement are set to 840-900°C, 840-900°C, 840-900°C, 840-900°C, 840-900°C, 840-900°C, and the advancement time is 380-460s.
[0028] In some embodiments of the present application, the temperatures of the six heating zones of the second advancement are set to 860-920°C, 860-920°C, 860-920°C, 860-920°C, 860-920°C, 860-920°C, and the advancement time is 320-400s.
[0029] In some embodiments of the present application, the temperatures of the six heating zones of the third advancement are set to 870-930°C, 870-930°C, 870-930°C, 870-930°C, 870-930°C, 870-930°C, and the advancement time is 200-280s.
[0030] In some embodiments of the present application, the screen-printed front graphic design is 16BB-196 grid.
[0031] In some embodiments of the present application, the above-mentioned 16BB-196 gate is specifically: 16 Y-direction main gates including harpoon design and PAD design, and 196 X-direction fine gates perpendicular to the main gates, the carrier transmission spacing between every two gate lines is 0.93㎜, a gradient line is set at the connection between the main and sub-gates, and the width of the fine gate is 10μm.
[0032] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0033] Example 1
[0034] This embodiment is a method for improving the efficiency of TOPCON batteries. The process includes entering the boat, vacuuming, leak detection, heating, the first step of deposition, the first step of advancement, the second step of deposition, the second step of heating and advancement, the third step of deposition, the third step of heating and advancement, heating and oxygen oxidation (to form a surface protection layer for the next step) and cooling and exiting the boat to complete the process. The improvement steps are specifically the deposition, advancement and corresponding screen printing in the boron diffusion step.
[0035] The improved deposition process is as follows: in the first deposition step, the O2 flow rate is 540 sccm, the BCl3 flow rate is 130 sccm, the temperatures of the six heating zones are set to 840°C, 840°C, 840°C, 840°C, 840°C, and the process time is 120 s;
[0036] In the second deposition step, the O2 flow rate was 560 sccm, the BCl3 flow rate was 160 sccm, the temperatures of the six heating zones were set to 840°C, 840°C, 840°C, 840°C, 840°C, and the process time was 210 s.
[0037] In the third deposition step, the O2 flow rate was 580 sccm, the BCl3 flow rate was 180 sccm, the temperatures of the six heating zones were set to 855°C, 855°C, 855°C, 855°C, 855°C, and the process time was 210 s.
[0038] The traditional one-step advancement process was improved to three steps, and the furnace tube temperature was lowered. Specifically, the temperatures of the six heating zones in the first advancement step were set to 870°C, 870°C, 870°C, 870°C, 870°C, and 870°C, and the advancement time was 420s.
[0039] In the second advancement step, the temperatures of the six heating zones were set to 890°C, 890°C, 890°C, 890°C, 890°C, 890°C, and 890°C, with an advancement time of 360s;
[0040] In the third advancement step, the temperatures of the six heating zones were set to 900°C, 900°C, 900°C, 900°C, 900°C, and 900°C, and the advancement time was 240s.
[0041] The corresponding screen-printed front graphic design is 16BB-196 grids; that is, 16 Y-direction main grids including harpoon design and PAD design, and 196 X-direction fine grids perpendicular to the main grids, with a carrier transmission spacing of 0.93mm between every two grid lines, and a gradient line at the connection between the main and sub-grids. After the improvement, the design width of the fine grid line is 10μm. The graphic structure design is the same as before the improvement, except that the number of fine grids is increased and the design line width of the fine grid is changed.
[0042] Example 2
[0043] This embodiment is a method for improving the efficiency of TOPCON batteries. The process includes entering the boat, vacuuming, leak detection, heating, the first step of deposition, the first step of advancement, the second step of deposition, the second step of heating and advancement, the third step of deposition, the third step of heating and advancement, heating and oxygen oxidation (to form a surface protection layer for the next step) and cooling and exiting the boat to complete the process. The improvement steps are specifically the deposition, advancement and corresponding screen printing in the boron diffusion step.
[0044] The improved deposition process is as follows: in the first deposition step, the O2 flow rate is 560 sccm, the BCl3 flow rate is 130 sccm, the temperatures of the six heating zones are set to 850°C, 850°C, 850°C, 850°C, 850°C, and 850°C, and the process time is 120 s;
[0045] In the second deposition step, the O2 flow rate is 560 sccm, the BCl3 flow rate is 160 sccm, and the temperatures of the six heating zones are set to 850°C, 850°C, 850°C, 850°C, 850°C, and 850°C, and the process time is 220 s.
[0046] In the third deposition step, the O2 flow rate is 600 sccm, the BCl3 flow rate is 180 sccm, the temperatures of the six heating zones are set to 860°C, 860°C, 860°C, 860°C, 860°C, and 860°C, and the process time is 220 s.
[0047] The traditional one-step advancement process was improved to three steps, and the furnace tube temperature was lowered. Specifically, the temperatures of the six heating zones in the first advancement step were set to 870°C, 870°C, 870°C, 870°C, 870°C, and 870°C, and the advancement time was 420s.
[0048] In the second advancing step, the temperatures of the six heating zones were set to 880°C, 880°C, 880°C, 880°C, 880°C, and 880°C, with an advancing time of 360 s.
[0049] In the third advancement step, the temperatures of the six heating zones were set to 900°C, 900°C, 900°C, 900°C, 900°C, and 900°C, and the advancement time was 240s.
[0050] The corresponding screen-printed front graphic design is 16BB-196 grids; that is, 16 Y-direction main grids including harpoon design and PAD design, and 196 X-direction fine grids perpendicular to the main grids, with a carrier transmission spacing of 0.93mm between every two grid lines, and a gradient line at the connection between the main and sub-grids. After the improvement, the design width of the fine grid line is 10μm. The graphic structure design is the same as before the improvement, except that the number of fine grids is increased and the design line width of the fine grid is changed.
[0051] Experimental example
[0052] This experimental example explores the effects of improvements on TOPCON batteries.
[0053] The control group uses the traditional three-step deposition + one-step advancement method, and the corresponding screen-printed front pattern is 16BB-172 grids. Its pattern design includes 16 Y-direction main grids including harpoon design and PAD design, and 172 X-direction fine grids perpendicular to the main grid. The carrier transmission spacing between every two grid lines is 1.11mm, and a gradient line is set at the connection between the main and auxiliary grids. The current production line fine grid line width design width is 12μm. Figure 1 shown.
[0054] The key process steps are three deposition steps. In the first deposition step, the O2 injection amount is 440sccm, the BCl3 injection amount is 110sccm, the temperatures of the six heating zones are set to 840℃, 840℃, 840℃, 840℃, 840℃, and the process time is 120s; in the second deposition step, the O2 injection amount is 440sccm, the BCL3 injection amount is 110sccm, the temperatures of the six heating zones are set to 840℃, 840℃, 840℃, 840℃, 840℃, and the process time is 210s; in the third deposition step, the O2 injection amount is 440sccm, the BCl3 injection amount is 110sccm, the temperatures of the six heating zones are set to 855℃, 855℃, 855℃, 855℃, 855℃, and the process time is 210s.
[0055] The temperatures of the six heating zones of the advancing step furnace tube are set to 910°C (conventionally between 880 and 940°C), 910°C, 910°C, 910°C, 910°C, 910°C, and 910°C, and the advancing time is 1020s.
[0056] The experimental group is an improved group, which adopts the process of Example 1 with three deposition steps + three advancements, and the corresponding screen printing front pattern design is 16BB-196 grids; that is, 16 Y-direction main grids including harpoon design and PAD design, and 196 X-direction fine grids perpendicular to the main grids, the carrier transmission spacing between every two grid lines is 0.93mm, and a gradient line is set at the connection between the main and sub-grids. After improvement, the design width of the fine grid line is 10μm. Figure 2 shown.
[0057] The matrix doping depth and doping concentration curves of the control group are shown in Figure 3 As shown, from Figure 3 It can be seen from the matrix doping depth and doping concentration curves that the measured surface concentration is 4.48E+18 (maximum value on the ordinate) and the junction depth is 0.9737μm (maximum value on the abscissa). The matrix doping depth and doping concentration curves of the experimental group are shown in Figure 1. Figure 4 As shown, from Figure 4 It can be seen that the matrix doping depth and doping concentration curves show that the measured surface concentration is 2.03E+18 (maximum value on the ordinate) and the junction depth is 0.8517 μm (maximum value on the abscissa).
[0058] The parameters and performance data of the control group and the experimental group are shown in Table 1.
[0059] Table 1
[0060]
[0061]
[0062] It can be seen from Table 1 that: 1. Compared with the control group, the total process time of boron diffusion after improvement is consistent with it, and has no effect on production capacity; 2. The experimental group adopts a distributed advancement method for step-by-step heating, which is conducive to the control of the advancement depth of boron ions and has better uniformity; 3. Compared with the control group, the surface concentration of the experimental group is lower after improvement, which increases the blue light response in the short-wave region, reduces the emitter defect density and reduces the recombination rate; 4. The 172 gate lines are changed to 196 gate lines. Through line width design, the front shading area of the experimental group is consistent with that of the control group, and has no effect on the light-receiving surface; 5. The experimental group reduces the transmission distance of carriers in the thin layer through dense grid design, reduces transmission losses, and improves conversion efficiency by 0.081%.
[0063] In summary, the method for improving the efficiency of TOPCON batteries in the embodiment of the present application has the following advantages:
[0064] 1. The improvement of the amount of O2 and BCl3 introduced in the three deposition steps in this application can reduce the surface concentration of the substrate and increase the blue light response and contact ability.
[0065] 2. The present application adjusts the traditional one-time total advancement into three-time distributed advancement and combines it with step temperature rise. The step temperature rise advancement process is beneficial to the control of the depth of boron ion advancement, making the uniformity of boron diffusion better, and the improved boron diffusion process time remains unchanged, so there is no adverse effect on production capacity.
[0066] 3. This application changes the 172 grid lines of traditional screen printing to 196 grid lines. Through line width design, the front shading area remains consistent with that before the improvement, and has no effect on the light-receiving surface; however, through dense grid design, the transmission distance of carriers in the thin layer is reduced, the transmission loss is reduced, and the conversion efficiency is improved by 0.081%.
[0067] In summary, compared with the traditional boron diffusion and metallization patterns, the improved process of the present application does not produce adverse effects, but can significantly improve the conversion efficiency and is worthy of popularization and application.
[0068] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.
Claims
1. A method for improving the efficiency of TOPCON batteries, characterized in that: This includes depositing, advancing and screen printing silicon wafers; The deposition includes three depositions: in the first deposition step, the O2 flow rate is 500-580sccm, the BCl3 flow rate is 70-190sccm, in the second deposition step, the O2 flow rate is 500-600sccm, the BCl3 flow rate is 100-210sccm, and in the third deposition step, the O2 flow rate is 520-640sccm, the BCl3 flow rate is 120-230sccm; The advancement includes three steps: the temperature of the first advancement step is 840-900°C, the temperature of the second advancement step is 860-920°C, and the temperature of the third advancement step is 870-930°C.
2. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones in the first deposition step are set to 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, and 810-870°C, and the deposition time is 80-130s.
3. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones in the second deposition step are set to 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, 810-870°C, and 810-870°C, and the deposition time is 180-230s.
4. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones in the third deposition step are set to 825-885°C, 825-885°C, 825-885°C, 825-885°C, 825-885°C, 825-885°C, and the deposition time is 180-230s.
5. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones of the first advancement are set to 840-900°C, 840-900°C, 840-900°C, 840-900°C, 840-900°C, 840-900°C, and 840-900°C, and the advancement time is 380-460s.
6. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones of the second advancement are set to 860-920°C, 860-920°C, 860-920°C, 860-920°C, 860-920°C, 860-920°C, and 860-920°C, and the advancement time is 320-400s.
7. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The temperatures of the six heating zones of the third advancement are set to 870-930°C, 870-930°C, 870-930°C, 870-930°C, 870-930°C, 870-930°C, and 870-930°C, and the advancement time is 200-280s.
8. A method for improving the efficiency of TOPCON batteries according to claim 1, characterized in that: The screen-printed front graphic design is 16BB-196 grid.
9. A method for improving the efficiency of TOPCON batteries according to claim 8, characterized in that: The 16BB-196 gate specifically includes: 16 Y-direction main gates including harpoon design and PAD design, and 196 X-direction fine gates perpendicular to the main gates. The carrier transmission spacing between every two gate lines is 0.93 mm. A gradient line is set at the connection between the main and sub-gates, and the width of the fine gate is 10 μm.